Strategi Pengembangan Kampung Seni Jurang Blimbing Tembalang - Yuventius Tyas Catur Pramudi; Doddy Reyhan Dhanniarto; Noval Ardianto (Badan Riset dan Inovasi Daerah Kota Semarang, 2026)
Jurang Blimbing Village in Tembalang, Semarang, is a thematic village rich in traditional arts and culture, including Ketoprak, Kuda Lumping, and Kaligrafi. This study aims to explore the potential of the village as a center for cultural tourism and its role in preserving local heritage. Through qualitative methods, including field observations and interviews with local communities, the research identifies strengths, weaknesses, opportunities, and threats (SWOT) to guide development strategies. Results indicate strong community engagement but limited promotion and infrastructural challenges. Recommendations include enhancing public awareness, improving infrastructure, and fostering continuous cultural education to sustain the village's cultural legacy.